2020
DOI: 10.32552/2020.actamedica.503
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase, Beta-2 Microglobulin Levels and CD4/CD8 Lymphocyte Ratio in Patients with Mycosis Fungoides in Stage 1A

Abstract: Objective: Mycosis fungoides is the most common type of primary cutaneous T-cell lymphomas. In this study, we aimed to investigate the biochemical parameters of beta-2 microglobulin, lactate dehydrogenase, CD4/CD8 lymphocyte ratio determined by flow cytometry, and T cell clonality in patients with MF and to correlate these parameters in stage 1A and other stages. Materials and Methods: A hundred sixty-one (87 Male, 74 Female) patients followed-up between January 1995 and January 2019 were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, our results need to be analyzed carefully given the heterogeneity of the entities considered. Several studies have demonstrated that LDH may be associated with later tumor stages and worse prognosis, particularly in MF and SS [27], whereas only hints of evidence of the role of beta-2M levels are present for cutaneous lymphomas [28]. Considering peripheral beta-2M and LDH levels, we observed a statistically significant difference between CTCL and CBCL (p = 0.025 and p < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 55%
“…However, our results need to be analyzed carefully given the heterogeneity of the entities considered. Several studies have demonstrated that LDH may be associated with later tumor stages and worse prognosis, particularly in MF and SS [27], whereas only hints of evidence of the role of beta-2M levels are present for cutaneous lymphomas [28]. Considering peripheral beta-2M and LDH levels, we observed a statistically significant difference between CTCL and CBCL (p = 0.025 and p < 0.001, respectively).…”
Section: Discussionmentioning
confidence: 55%
“…Diamandidou et al 23 concluded raised serum Beta‐2 microglobulin and LDH levels were predictive of LCT in early‐stage MF patients. In another study including 161 patients, no significant differences in LDH levels were observed between stage IA and other stages 24 . In PROCLIPI study, LDH levels were elevated in 27 of the patients with early‐stage disease.…”
Section: Lactate Dehydrogenase Levels and Prognosismentioning
confidence: 89%
“…In another study including 161 patients, no significant differences in LDH levels were observed between stage IA and other stages. 24 In PROCLIPI study, LDH levels were elevated in 27 of the patients with early-stage disease. Stage IIA showed higher LDH levels (43.5%) compared to stage IA and IB (6.7% and 8.9%, respectively).…”
Section: Ac Tate Dehydrog Ena S E Le Vel S and Prog Nos Ismentioning
confidence: 93%